Predicting Geographic Ranges of Marine Animal Populations Using Stable Isotopes: A Case Study of Great Hammerhead Sharks in Eastern Australia - Raoult, Vincent; Trueman, Clive N.; Kingsbury, Kelsey M.; Gillanders, Bronwyn M.; Broadhurst, Matt K.; Williamson, Jane E.; Nagelkerken, Ivan; Booth, David J.; Peddemors, Victor; Couturier, Lydie I. E.; Gaston, Troy F. (Frontiers in Marine Science, 2020)
Determining the geographic range of widely dispersed or migratory marine organisms is notoriously difficult, often requiring considerable costs and typically extensive tagging or exploration programs. While these approaches are accurate and can reveal important information on the species, they are usually conducted on only a small number of individuals and can take years to produce relevant results, so alternative approaches may be preferable. The presence of latitudinal gradients in stable carbon isotope compositions of marine phytoplankton offers a means to quickly determine likely geographic population ranges of species that rely on productivity from these resources. Across sufficiently large spatial and temporal scales, the stable carbon isotopes of large coastal or pelagic marine species should reflect broad geographic patterns of resource use, and could be used to infer geographic ranges of marine populations. Using two methods, one based on a global mechanistic model and the other on targeted low-cost latitudinal sampling of fishes, we demonstrate and compare these stable isotope approaches to determine the core population geography of an apex predator, the great hammerhead (Sphyrna mokarran). Both methods indicated similar geographic ranges and suggested that S. mokarran recorded in south-eastern Australia are likely to be from more northern Australian waters. These approaches could be replicated in other areas where coastlines span predictable geographic gradients in isotope values and be used to determine the core population geography of highly mobile species to inform management decisions.